Exploring The Concept of Gratitude in Family Happiness: Insights from Maluku Society - Rampisela, Theophanny Paula Theresia; Korlefura, Criezta (KnE Social Sciences, 2024)
Gratitude is a fundamental aspect of human experience, deeply intertwined with happiness and well-being, especially within the unique cultural context of Maluku society. This qualitative study aims to explore the concept of gratitude within Maluku families and its significance in nurturing familial well-being. Through interviews with five Christian families in Amahusu, Ambon, the study examines key aspects of gratitude. The findings reveal that family happiness in Maluku is grounded in positive interactions, spiritual values, personal achievements, and social relationships. Gratitude emerges as a crucial factor, shaping perceptions of happiness across various life circumstances. Particularly the emphasis on gratitude in confronting challenges, with faith and prayer serves as the essential coping mechanisms. Despite adversities, families maintain an optimistic outlook, deriving happiness from simplicity and social bonds. Thematic analysis of interview data unveils recurring themes, patterns, and insights about gratitude and familial happiness. By amalgamating qualitative inquiry with thematic analysis, this study endeavors to furnish a comprehensive understanding of gratitude's role in nurturing family happiness within Maluku society. Enriched by poignant narrative accounts and profound participant insights, this research contributes to the corpus of knowledge on gratitude and its implications for familial well-being across diverse cultural milieus. Keywords: gratitude, family happiness, Maluku